Digitalization of accounting: current trends and automation tools (Economics and region, 2024)
Digital technologies have long been an integral part of global accounting. However, their implementation in Ukrainian enterprises has begun relatively recently. The current study is devoted to substantiating the importance of introducing digital technologies in modern accounting processes of an enterprise. The research was carried out with the help of systematization methods - to reveal the existing automation tools in accounting in modern conditions of digitization, the analysis method - to evaluate the existing scientific base of research on the chosen topic, as well as methods of induction and deduction and generalization to form further trends in the development of digital automation tools. The study carefully systematizes the tools for automating accounting processes in the context of digitalization, which have a significant impact on the efficiency of accounting in Ukraine. It is established that successful automation involves the integration of the latest technologies, such as artificial intelligence, blockchain, cloud solutions, analytical systems, etc. It is found that these technologies help to optimize accounting procedures, improve data accuracy, and ensure transparency and accessibility of information for all stakeholders. The author also summarizes further trends in the introduction of digital technologies in the transformational conditions of Ukraine, which include adaptation to new market requirements, development of accountants' qualifications and integration of innovative solutions into business processes. It is established that successful digitalization of accounting requires not only the implementation of technical changes, but also a change in management approaches, which is justified by the needs of modern entrepreneurship in Ukraine. The study emphasizes the importance of formulating digitalization strategies that take into account the specifics and characteristics of the Ukrainian market, in particular, its transformational challenges. Further research should be aimed at studying the impact of each digital tool on the organization of accounting at modern Ukrainian enterprises.
Keywords: artificial intelligence; blockchain technologies; cloud technologies; process automation; record keeping